COVID-19 knowledge, attitudes and practices in Thabo Mofutsanyana District, South Africa, 2022 - Inge Kleinhans; Siphesihle K. Mahanjana; Lehlohonolo Kumalo; Brian Brümmer; Ashley Chitaka; Zandile D. Nukeri; Fiona Els; Sizeka Mashele; Michelle Groome; Natalie Mayet; Ramasedi S. Mokoena; Emily B. Atuheire; et al. (Journal of Public Health in Africa)
Background: Adherence to COVID-19 prevention and control measures is related to people’s knowledge, attitudes and practices.